2020
DOI: 10.1039/d0tc01367f
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties of epitaxial TmFe2O4 thin films with an anomalous interfacial structure

Abstract: Epitaxial TmFe2O4 thin film with self-assembled interface structure was grown on yttria-stabilized zirconia substrate. TmFe2O4 phase itself shows glassy behavior and the interface leads to the exchange bias effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…It must be mentioned that the remanent magnetization values at lower temperatures were comparable to those of bulk single crystals, 7,32 and were more than one order of magnitude larger than those of thin film samples in earlier studies. 19,20,22,23,25,26 The large deviation between the field-cooled (FC) and zero-field-cooled (ZFC) curves in Figure S2 indicates that the obtained films possessed large uniaxial magnetic anisotropy along the c-axis. Thus the ZFC magnetization curves had a sharp cusp 33 near the TN even with a magnetic field of 5 kOe.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It must be mentioned that the remanent magnetization values at lower temperatures were comparable to those of bulk single crystals, 7,32 and were more than one order of magnitude larger than those of thin film samples in earlier studies. 19,20,22,23,25,26 The large deviation between the field-cooled (FC) and zero-field-cooled (ZFC) curves in Figure S2 indicates that the obtained films possessed large uniaxial magnetic anisotropy along the c-axis. Thus the ZFC magnetization curves had a sharp cusp 33 near the TN even with a magnetic field of 5 kOe.…”
Section: Resultsmentioning
confidence: 99%
“…37,38 High-angle annular dark field HRTEM images indicated that the epitaxial LuFe2O4/TmFe2O4 films on YSZ (111) contained the hexagonal LuFeO3/TmFeO3 layers as the first or buffer layer on the substrate. 19,20 In addition, according to molecular dynamics simulation of the interface between hexagonal LuFeO3 and YSZ (111), the Fe 3+ ions were considered to have been placed directly on the O 2ion of oxygen-terminated surface. 39 Analogous to their results, the prospective atomic structures of the interface between YSZ (111) and YbFe2O4 (0001) are illustrated in Figure 6.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To apply electronic ferroelectricity observed in a bulk YbFe 2 O 4 to future ferroelectric devices, thin film crystals have been fabricated [13][14][15][16][17]. Several studies have succeeded in the epitaxial growth of YbFe 2 O 4 thin films on various substrates, including yttriumstabilized zirconia (YSZ) [13][14][15], MgO [16], and α-Al 2 O 3 [17,18], whose structures are compatible with the hexagonal lattice of RFe 2 O 4 .…”
Section: Introductionmentioning
confidence: 99%
“…To apply electronic ferroelectricity observed in a bulk YbFe 2 O 4 to future ferroelectric devices, thin film crystals have been fabricated [13][14][15][16][17]. Several studies have succeeded in the epitaxial growth of YbFe 2 O 4 thin films on various substrates, including yttriumstabilized zirconia (YSZ) [13][14][15], MgO [16], and α-Al 2 O 3 [17,18], whose structures are compatible with the hexagonal lattice of RFe 2 O 4 . Furthermore, based on transmission electron microscopy (TEM) observations, Fujii et al [14,17] first discovered that the resulting YbFe 2 O 4 films have a superlattice structure owing to the order of Fe ions having the same three-fold periodicity as single crystals [4,19].…”
Section: Introductionmentioning
confidence: 99%